Pelatihan Komunikasi Efektif, Supervisi dan Masa Kerja Perawat terhadap Perilaku Caring Perawat - Hutagalung, Rosmaniar Evalina; Bunga, Asnet Leo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of practical communication training, supervision, and length of service on nurses' caring behavior in nursing care. The method used is a literature review study using the PubMed, ScienceDirect, Semantic Scholar, and Google Scholar databases for publications on